1967
DOI: 10.1037/h0025065
|View full text |Cite
|
Sign up to set email alerts
|

Communication of affects between feral and socially isolated monkeys.

Abstract: 3 rhesus monkeys were obtained from the Regional Primate Center, University of Wisconsin. These animals had been subjected to total social isolation during their 1st yr. of life. 3 feral monkeys of the same age constituted the normal group. The animals were trained to perform an instrumental avoidance response to a visual stimulus. There were no differences in acquisition of the response either in terms of instrumental behavior or conditioned cardiac responses. The animals were then paired in all possible comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(48 citation statements)
references
References 13 publications
(20 reference statements)
1
47
0
Order By: Relevance
“…However, these socially deprived animals proved difficult to test in the laboratory because of their heightened emotional reactivity, leading researchers to redirect their studies to emotional processes and behavioral regulation (Harlow et al, 1971). Similarly, isolate-reared monkeys were found to be impaired at both sending and receiving emotional cues to conspecifics (Miller, Caul, & Mirsky, 1967). Rodent studies first implicated the hypothalamic-pituitary-adrenocortical (HPA) axis and its limbic-cortical regulatory pathways in these effects (Liu, Diorio, Day, Francis, & Meaney, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, these socially deprived animals proved difficult to test in the laboratory because of their heightened emotional reactivity, leading researchers to redirect their studies to emotional processes and behavioral regulation (Harlow et al, 1971). Similarly, isolate-reared monkeys were found to be impaired at both sending and receiving emotional cues to conspecifics (Miller, Caul, & Mirsky, 1967). Rodent studies first implicated the hypothalamic-pituitary-adrenocortical (HPA) axis and its limbic-cortical regulatory pathways in these effects (Liu, Diorio, Day, Francis, & Meaney, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars' definitions of nonverbal communication widely vary, but most agree that it means using all communication methods other than language. For example, Miller et al (1967) said that nonverbal communication was closely related to intentional behaviors, Samover et al (1981) that it was stimuli with the form of messages other than language in communication, and Dodd (1982) that it was a communication to express intentions using gestures, time and space. In communication in general, and service provision in particular, nonverbal communication plays a large part because the communicator cannot perfectly express what he or she intends to deliver with verbal communication alone.…”
Section: Nonverbal Communicationmentioning
confidence: 97%
“…Several studies employing rhesus macaques as subjects have demonstrated the important roles of both early experience and maturation in the development of affective perceptual capabilities [Kenney et al, 1979;Miller et al, 1967;Sackett, 1965, 19661. To date, however, no studies have been conducted on the process of affect perception in normally reared adult primates.…”
Section: Introductionmentioning
confidence: 99%